PENGARUH SERTIFIKAT TANAH SEBAGAI AKSES AGUNAN KREDIT: IMPLIKASI BAGI KESEJAHTERAAN MASYARAKAT DAN PEMBERDAYAAN EKONOMI DI INDONESIA - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (CV. ADIBA AISHA AMIRA, 2025)
This study examines the impact of land certificates as collateral for credit access on community welfare and economic empowerment in Indonesia through a literature review approach. Land certificates serve as legal collateral that enables communities to obtain credit from formal financial institutions more easily, thereby opening up opportunities to improve income, education, health, and overall living standards. In addition, land certificates also play an important role in expanding financial inclusion and encouraging the development of micro, small, and medium enterprises as a form of sustainable economic empowerment. However, there are challenges and risks, such as the risk of asset loss due to default and low financial literacy, which must be overcome with policy support, education, and legal protection. The results of this study confirm that land certificates are a strategic instrument in efforts to promote inclusive and sustainable community welfare and economic empowerment in Indonesia.